2020
DOI: 10.1101/2020.07.30.228650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic suppression of SLFN11 in germinal center B cells in the process of the dynamic expression change during B-cell development

Abstract: <strong>Background</strong>   SLFN11 enhances cellular toxicity of genotoxic anti-cancer agents, and its important role under physiological conditions has not been appreciated yet. Somatic hypermutations and class switch recombination that can cause physiological genotoxic stress arise in germinal center B cells (GCBs). GCBs are a major origin of B-cell lymphomas that are frequently treated by cytosine arabinoside, a genotoxic anti-cancer agent.   <strong>Objective</strong>   To clarify… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The present case had a relatively high expression of SLFN11 by immunohistochemistry, suggesting sensitivity to chemotherapy (Figure 2C). Interestingly, a recent report suggests that non-germinal center B (non-GCB)-type lymphomas, the predominant type in PCNSL, have higher SLFN11 compared to GCB-type [11], although SLFN11 expression in PCNSL has not been studied to date. We analyzed the CellMinerCDB database and found that there was a weak, positive correlation between SLFN11 expression and sensitivity to methotrexate in lymphoma cell lines (r = 0.44, Supplemental figure 1) [12].…”
Section: Discussionmentioning
confidence: 99%
“…The present case had a relatively high expression of SLFN11 by immunohistochemistry, suggesting sensitivity to chemotherapy (Figure 2C). Interestingly, a recent report suggests that non-germinal center B (non-GCB)-type lymphomas, the predominant type in PCNSL, have higher SLFN11 compared to GCB-type [11], although SLFN11 expression in PCNSL has not been studied to date. We analyzed the CellMinerCDB database and found that there was a weak, positive correlation between SLFN11 expression and sensitivity to methotrexate in lymphoma cell lines (r = 0.44, Supplemental figure 1) [12].…”
Section: Discussionmentioning
confidence: 99%
“…The present case showed a relatively high expression of SLFN11 by immunohistochemistry, suggesting sensitivity to chemotherapy ( Figure 2 C). Interestingly, a recent report suggested that nongerminal center B (non-GCB)-type lymphomas, the predominant type in PCNSLs, have higher SLFN11 levels than the GCB-type ones [ 15 ], although the SLFN11 expression in PCNSLs has not been studied to date. We analyzed the CellMinerCDB database and found a weak positive correlation between the SLFN11 expression and the sensitivity to methotrexate in lymphoma cell lines (r = 0.44, Supplemental Figure S1 ) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, SLFN11 targets DNA replication by binding to replication forks via replication protein A1 (RPA1) (2,3), blocking the replicative helicase complex (3), inducing the degradation of the replication initiation factor CDT1 (4) and stalled replication forks (5) and causing chromatin opening with activation of the stress response and immediate early response genes (IEGs) (6). Because approximately 50% of cancer cell lines and a large fraction of patient tumors do not express SLFN11 and are resistant to DNA replication-targeted therapies (1,(7)(8)(9)(10)(11)(12)(13)(14)(15), an unanswered question is how to target SLFN11-negative cancer cells.…”
Section: Introductionmentioning
confidence: 99%